Scene, production and moqueca: Dimenti´s (1998-2012) bahian contemporary theater: (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article aimed to make visible a part of the recent history of Bahia´s (mainly Salvador) performing arts, by approaching Dimenti (1998-2012), a group in which I participated – this participation makes me a privileged witness of its aesthetic purposes, rehearsal practices and staging – of its history. By chronologically describing its plays, it is possible to notice a group with an intense production, interested in a profound dialogue with other languages. From the description of this small part of Bahia´s theater, we conclude that, within Nordeste’s theater, there are many theaters – from more traditional to more experimental ways of staging; artistic purposes and diverse topics – which inject complexity and dissent in the ways Brazilian theater became modern.
Keywords: Theater; Dance; Dimenti; Bahia; Nordeste